Determinants of Final Consumption Expenditure in Nepal (The Journal of Economic Concerns, 2025)
This paper explores the reciprocal relationship between urbanization, remittance inflows, and GDP growth as determinants of Final Consumption Expenditure (FCE) in Nepal. The analysis serves as an empirical case study of a Least Developed Country (LDC) navigating a unique economic landscape. Since understanding consumer behavior is critical for overall economic development, this research focuses on the aforementioned determinants as key drivers of consumption spending. By utilizing secondary data from reliable sources, the study scrutinizes the influence of these factors on consumer behavior. Nepal’s FCE model offers a unique perspective on transitional economies, providing valuable insights for policy formulation in similar contexts. Ultimately, this paper highlights the transition from consumption-led growth toward investment-oriented development to achieve sustainable economic stability, revealing the vital connections between FCE determinants and their broader economic impact.